Grading adaptation for students with hearing impairments in WBL (Work-based learning) subjects: A preliminary study - Setuju, Setuju; Andini, Dinar Westri; Inderanata, Rochmad Novian; Suyitno, Suyitno; Marsono, Marsono (Edelweiss Applied Science and Technology, 2024)
The implementation of adaptive assessment models for students with hearing impairments in work-based learning (WBL) courses is essential to fostering an inclusive educational environment that accommodates diverse learning needs. This study purposes to identify and describe the adaptive assessment requirements for deaf students in inclusive schools, providing valuable insights for teachers in creating fair and accommodating assessment methods. The study method used a qualitative descriptive research design with observation, interviews and documentation techniques. Data analysis was carried out using the Miles and Huberman model including data collection, data reduction, data display and drawing conclusion or verification. The finding shows that the teachers at SMK Muhammadiyah 3 Yogyakarta and Pondok Pesantren Tuna Rungu emphasize the importance of adaptation in the assessment and learning system for students with hearing impairments, especially in the field of welding skills. Teachers express the necessity of an assessment approach that is not only fair but also allows students to showcase their competencies effectively despite their hearing limitations. The conclusion is a more effective and inclusive learning environment for people with hearing impairments can develop students’ skills and make them feel valued in their learning process. The practical implications are designing and developing assessment models with inclusive standards to ensure effective learning outcomes for students with hearing impairments in vocational education environments.